Automated Measurement of Levitation Force Using Labview Programming Language - Mohamed Shariff, Abdul Majeed (2006)
This study deals with the development of an automated system for the investigation of levitation forces through three sets of experiments. The first set is a study of levitation forces between moving superconductors or conductors with a permanent magnet. The superconductors were used in field cooled and zero field cooled states. The second set deals with the study of levitation forces between a moving small discs shaped magnet with a much larger square magnet. The third set deals with the study of levitation forces between two identical magnets with a superconductor placed between them. An automated experimental setup was successfully setup that uses a computer, together with the LabVIEW software, an electronic balance, a DC motor controlled by a PWM circuit, a rpm sensor circuit and an actuator to achieve the stated objectives. The superconductors used were Bi1.6Pb0.4Sr2Ca2-xCdxCu3O10 (where x=0.00(pure), x=0.02, x=0.05, x=0.07 and x=0.1).. The conductors used were copper and aluminium of various thicknesses. The levitation force between a moving conductor and a permanent magnet can be measured and compared to it’s calculated values. It was shown that the levitation forces can be used to find the lift off speed of aluminium of thickness 4.75 mm to be 14.88 m/s. The first set of experiments revealed that levitation forces are depended upon the speed of the moving conductors but not on moving superconductors. It was also found that the levitation forces for superconductors are stronger in the zero field cooled states then the field cooled state. The second set of experiments showed that the levitation force between two magnets varies in a rotating field. The third set of experiments showed that the levitation forces between two identical magnets are not affected by the presence of a disc shaped superconductor. The system that has been developed can be used as an effective teaching aid for the teaching of magnetic levitation principles.